Microbiological characteristics of marketed rohu (Labeo rohita) - Sinha, D K; Choudhary, S P; Narayan, K G (Indian Journal of Fisheries, 2011)
Consumption of fish and fish products isnot always safe. At times, these contain microorganismsof public health significance,viz. Escherichia coli (Saxena et al. 1987),Staphylococcus (Sanjeev et al. 1985), Clostridiumperfringtns. Salmonella and others(Shewan 1962, Annymous 1974). The presentinvestigation rep arts the microbial flora ofmarketed rohu.